Reproductive effects of the tumor necrosis factor (TNF) deficiency in mice - S. O. Maslennikova; G. V. Kontsevaya; M. A. Zolotykh; M. V. Anisimova; N. A. Feofanova; M. P. Moshkin; S. A. Nedospasov; L. A. Gerlinskaya (Вавиловский журнал генетики и селекции, 2015)
TNF is a multifunctional cytokine that, at physiological concentrations, maintains the balance between apoptosis and survival of male germ cells and, at higher concentrations, has adverse effects on various stages of the reproductive process. Although ant-cytokine therapies have been used in millions of patients, the consequences of cytokine deficiency for reproductive functions are poorly understood and need attention. In this work, we have studied behavioral interactions between males and females, spermatogenesis, male fertility, and embryonic developmental characteristics of the progeny in TNFα knockout mice (TNF-/-). We have demonstrated that TNF is involved in the regulation of sexual behavior, spermatogenesis, pre- and postimplantation development. Complete TNF deficiency led to decreased reproductive efficiency: a lower number of viable embryos were observed in TNF-/- mice than in wild-type mice. The decrease in fertility was caused by preimplantation embryo loss in TNF-/- mice. Preimplantation loss in females might be caused by asospermia in TNF-/- males. Additionally, the sensitivity of reproductive functions to female stimuli was different between TNF-/- mice and wild-type mice, while interactions with females increased the concentrations of spermatozoids in both TNF-/- and wild-type mice. Still higher levels were observed in knockout animals, which led to increase in the number of immature spermatozoids in epididymides.